Structure-Function Correlation Analysis of Connexin50 Missense Mutations Causing Congenital Cataract: Electrostatic Potential Alteration Could Determine Intracellular Trafficking Fate of Mutants. (6th May 2014) - Sarkar, Devroop; Ray, Kunal; Sengupta, Mainak
Abstract : Connexin50 (Cx50) mutations are reported to cause congenital cataract probably through the disruption of intercellular transport in the lens. Cx50 mutants that undergo mistrafficking have generally been associated with failure to form functional gap junction channels; however, sometimes even properly trafficked mutants were found to undergo similar consequences. We hereby wanted to elucidate any structural bases of the varied functional consequences of Cx50 missense mutations through in silico approach. Computational studies have been done based on a Cx50 homology model to assess conservation, solvent accessibility, and 3-dimensional localization of mutated residues as well as mutation-induced changes in surface electrostatic potential, H-bonding, and steric clash. This was supplemented with meta-analysis of published literature on the functional properties of connexin missense mutations. Analyses revealed that the mutation-induced critical alterations of surface electrostatic potential in Cx50 mutants could determine their fate in intracellular trafficking. A similar pattern was observed in case of mutations involving corresponding conserved residues in other connexins also. Based on these results the trafficking fates of 10 uncharacterized Cx50 mutations have been predicted. Further experimental analyses are needed to validate the observed correlation.